Trends in media framing of China’s engagement in Africa and other parts of the world (2018)
This work critically examines studies that have researched on media framing of China’s engagement in different nations of the world. It dissects existing literature in the context of media coverage of China’s engagement in Africa and other nations. It tries to find out the most frequently adopted research method in studies investigating media coverage of China’s engagement in other countries; to examine the sampling techniques adopted in studies investigating media coverage of China’s engagement in other nations; to find out the methods of data analysis adopted in studies investigating media coverage of China’s engagement in other countries. Framing theory forms the theoretical basis for this study. The research method is content analysis while the study gathered data from various scholarly articles published in recognised academic journals and thesis accessed online through Google Scholar and Proquest. The articles were collated and identified based on those that focused their issues on media portrayal of China in other countries especially African nations. Findings show that majority of the studies adopted Content Analysis as their research method. Most of the reviewed studies (93.4%) were conducted in African nations. Also, most of the reviewed studies (80%) adopted purposive sampling technique. In addition, most of the reviewed studies employed deductive frame analysis as their method of data analysis. Seven of the reviewed articles used deductive frame analysis in that regard. This study suggested that more research should study media framing of China's engagement in other nations through different research approaches in order to understand China’s engagement more appropriately. It is recommended that other studies should engage the media audiences to know their perception of China’s engagement in their respective nations.